MANAJEMEN PENDIDIKAN KARAKTER DI SEKOLAH - Mukhtar Hadi (Ri'ayah: Jurnal Sosial dan Keagamaan, 2021)
The main problem of education is actually the issue of inculcating character values ​​in students. But in reality schools often ignore or are less serious about this character education issue. The cultivation of knowledge is considered more important than the cultivation of character values. Therefore, it is factual if there is a weakness in the character of students which in the end also results in the weakness of the nation's character. This paper aims to explain the importance of character education and the efforts that can be made by principals through the management of character education in schools. By implementing management functions which include four main functions of management, namely planning, organizing, actuating, and controlling, character education in schools can be managed and implemented in a planned, measurable and continuously evaluated. Through the implementation of the management functions of character education in schools, it must be a shared awareness and responsibility between the principal, teachers, parents and students themselves. Character education in schools is a deliberate and well-planned program. The implementation of character education in schools is carried out by integrating character content in all subjects and practiced in the teaching and learning process. Character education in schools is also carried out by creating a conducive school environment for the growth of a strong character culture, habituation and role model for all school families.